Modeling capillary wick irrigation system for greenhouse crop production - Roonjho, Shaheen Javed; Md Kamal, Rowshon; Roonjho, Abdul Rehman (Elsvier, 2022)
Microirrigation system is an efficient irrigation method that saves up to 60% of water and nutrients. However, the huge investment for installation of modern microirrigation systems is beyond of many smallholder crop producers. Therefore, this study focuses to model and develop the capillary wick irrigation system for greenhouse crop production to address this issue. The results revealed on tested wick materials that the maximum capillary height and maximum water holding capacity were observed in cotton bonded non-woven wick material compared to other materials (p > 0.05). Water level, wick length, and pot size linearly affected the discharge of wick emitter in hanging and buried capillary wick irrigation system (CWIS). In this study, the discharge equations for wick emitter of hanging and buried CWIS were successfully developed. Comparison of calculated discharge using newly developed equation with actual measured discharge of buried wick for potted tomatoes in greenhouse proved the accuracy of the equation. The effects of evapotranspiration were also found linearly on discharge of wick emitter and the relation between emitter discharge, pot size and evapotranspiration were lead the development of wick discharge linear curve (WDLC). WDLC introduced to estimate the required discharge for potted crops under CWIS. Then, solver program was used to successfully simulate the wick discharge for different potted crops under a CWIS. Outcomes of the study can be beneficial for smallholder farmers for greenhouse crop production for adopting CWIS as low-cost and highly efficient microirrigation system.